(untitled) (Global Journal of Computer Science and Technology, 2019)
Following the recent ban on plastic waste import by China developed countries face challenges with a high amount of plastic waste Plastic waste has been diverted to developing East-Asia countries like the Philippines Vietnam and Malaysia The Malaysian government has taken strict action to send back over 3000 tons of contaminated plastic waste This paper aims to establish mechanisms to detect the status of post-consumer PET bottles for recycling A research-based and experimental design approach was adopted to develop mechanisms to detect PET bottle status to ensure high-quality bottles A total of 1749 images were captured using a Raspberry Pi camera belonging to four different classes seal cap seal cap no seal cap content Deep Learning technology SqueezeNet was used to train the PET bottle images The trained model achieved 98 accuracy with correct bottle status recognized The model was deployed on a Raspberry Pi to detect PET bottles in real-time The model showed a delay of 0 018 to 0 022 seconds per prediction using Intel CPU in prediction performance Whereas on Raspberry Pi the prediction performance is 5 to 10 times slower than the Intel CPU with a delay of 0 1 to 0 25 seconds per prediction